BENTUK PENYAJIAN TATAK NANDORBIN PADA MASYARAKAT PAKPAK DI KECAMATAN SALAK KABUPATEN PAKPAK BHARAT - ROSALYATI ANGGRAINI (Universitas Negeri Medan, 2014)
The research was conducted at the end of November until the end of January 2015. The population and sample includes leaders in the community who know the culture Nandorbin hairline finish in Sub Salak, artists who know about the hairline finish Nandorbin, data collection is done by the method of field work which includes several aspects: observation, interviews, literature study, and documentation. Later in the analysis with qualitative descriptive method. Based on research that has been done, the form of presentation Nandorbin hairline finish on the pull with seven female dancers and one male dancer. There are nine varieties of motion at the beginning of Mertopak Nandorbin hairline finish, Menjengkur, Menjengkur menengen pasangen kamuhun direction, Menjengkur menengen pasangen kambirang direction, Menengen da Beru sideban, Menengen de Beru here select. Clothing on male dancers use of topical perbunga headgear mbacang, pakpak customary black shirt, and black pants. While the clothing worn women's clothing female dancers are called Merapi-fire, hood made of Ulos perdabaitak named saong Tonjong, gloves used is Oles Perdabaitak, and waist straps aluminum. Keywords: Tatak Nandorbin